Numerical modeling of oscillating Taylor bubbles - Ambrose, S.; Hargreaves, David; Lowndes, Ian (Taylor & Francis, 2016)
In this study, computational fluid dynamics (CFD) modeling is used to simulate Taylor bubbles rising in vertical pipes. Experiments indicate that in large diameter (0.29 m) pipes for an air–water system, the bubbles can rise in a oscillatory manner, depending on the method of air injection. The CFD models are able to capture this oscillatory behavior because the air phase is modeled as a compressible ideal gas. Insights into the flow field ahead and behind the bubble during contraction and expansion are shown. For a bubble with an initial pressure equal to the hydrostatic pressure at its nose, no oscillations are seen in the bubble as it rises. If the initial pressure in the bubble is set less than or greater than the hydrostatic pressure then the length of the bubble oscillates with an amplitude that depends on the magnitude of the initial bubble pressure relative to the hydrostatic pressure. The frequency of the oscillations is inversely proportional to the square root of the head of water above the bubble and so the frequency increases as the bubble approaches the water surface. The predicted frequency also depends inversely on the square root of the average bubble length, in agreement with experimental observations and an analytical model that is also presented. In this model, a viscous damping term due to the presence of a Stokes boundary layer for the oscillating cases is introduced for the first time and used to assess the effect on the oscillations of increasing the liquid viscosity by several orders of magnitude.